A progress report on Nene Branta sandvicensis in Hawaii Volcanoes National Park from 1974-89 - Hoshide, Howard M; Price, A Julie; Katahira, Lawrence (Wildfowl, 1990)
Hawaii Volcanoes National Park has supported a Nene Reintroduction Programme since 1974. The Resources Management Division is responsible for the management and monitoring of birds within and adjacent to the Park boundaries. The management aim has been to work toward the production of a wild, self-sustaining population. The method employed in order to achieve this has been to release captive-bred Nene into the wild. To date, a total of 177 birds has been released and monitored in and near the Park. This report summarises progress over the last 15 years.